SIV/SARS-CoV-2 coinfection in rhesus macaques impacts viral shedding, host immunity, the microbiome, and viral evolution - Fredericks, Megan N.; Kolodner, Zohar; Waalkes, Adam; Sawatzki, Kaitlin; Hao, Linhui; Long, Dustin R.; Penewit, Kelsi; Midkiff, Cecily C.; McCormick, Carter J.; Beraki, Semira; Edlefsen, Paul T.; Barrow, Jeana; et al. (Frontiers in Immunology, 2025)
People living with HIV (PLWH) have an increased risk of severe COVID-19, including prolonged viral shedding and emergence of mutations. To investigate the simian immunodeficiency virus (SIV) macaque model for HIV/SARS-CoV-2 coinfection, seven SIV+ rhesus macaques were co-infected with SARS-CoV-2. COVID-19 in all macaques was mild. SARS-CoV-2 replication persisted in the upper, but not the lower respiratory tract for 14 days post-infection. Animals showed impaired generation of anti-SARS-CoV-2 antibodies and T-cells. Animals also displayed transient changes in microbial communities in the upper airway and gastrointestinal tract. Evidence of SARS-CoV-2 evolution was observed in the upper respiratory tract. This study demonstrates that SIV/SARS-CoV-2 coinfection in rhesus macaques recapitulates aspects of COVID-19 in PLWH. We show that SIV impairs anti-SARS-CoV-2 immunity, potentially leading to prolonged viral shedding, altered pathogenesis, and viral evolution. This highlights the importance of HIV status in COVID-19 and supports the use of this model for HIV/SARS-CoV-2 coinfection.